Reducing Glucokinase Activity Restores Endogenous Pulsatility and Enhances Insulin Secretion in Islets From db/db Mice - Jahan, Ishrat (Endocrinology, 2018)
An early sign of islet failure in type 2 diabetes (T2D) is the loss of normal patterns of pulsatile insulin release. Disruptions in pulsatility are associated with a left shift in glucose sensing that can cause excessive insulin release in low glucose (relative hyperinsulinemia, a hallmark of early T2D) and β-cell exhaustion, leading to inadequate insulin release during hyperglycemia. Our hypothesis was that reducing excessive glucokinase activity in diabetic islets would improve their function. Isolated mouse islets were exposed to glucose and varying concentrations of the glucokinase inhibitor d-mannoheptulose (MH) to examine changes in intracellular calcium ([Ca(2+)](i)) and insulin secretion. Acutely exposing islets from control CD-1 mice to MH in high glucose (20 mM) dose dependently reduced the size of [Ca(2+)](i) oscillations detected by fura-2 acetoxymethyl. Glucokinase activation in low glucose (3 mM) had the opposite effect. We then treated islets from male and female db/db mice (age, 4 to 8 weeks) and heterozygous controls overnight with 0 to 10 mM MH to determine that 1 mM MH produced optimal oscillations. We then used 1 mM MH overnight to measure [Ca(2+)](i) and insulin simultaneously in db/db islets. MH restored oscillations and increased insulin secretion. Insulin secretion rates correlated with MH-induced increases in amplitude of [Ca(2+)](i) oscillations (R(2) = 0.57, P < 0.01, n = 10) but not with mean [Ca(2+)](i) levels in islets (R(2) = 0.05, not significant). Our findings show that correcting glucose sensing can restore proper pulsatility to diabetic islets and improved pulsatility correlates with enhanced insulin secretion.